2021
DOI: 10.3390/ijms22115840
|View full text |Cite
|
Sign up to set email alerts
|

DArTseq-Based High-Throughput SilicoDArT and SNP Markers Applied for Association Mapping of Genes Related to Maize Morphology

Abstract: Today, agricultural productivity is essential to meet the needs of a growing population, and is also a key tool in coping with climate change. Innovative plant breeding technologies such as molecular markers, phenotyping, genotyping, the CRISPR/Cas method and next-generation sequencing can help agriculture meet the challenges of the 21st century more effectively. Therefore, the aim of the research was to identify single-nucleotide polymorphisms (SNPs) and SilicoDArT markers related to select morphological feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This approach can generate SNP markers with higher numbers covering the plants’ whole genome ( Akbari et al, 2006 ; Raman et al, 2014 ; Barilli et al, 2020 ) and is successfully used in several crops, including pea ( Aznar-Fernández et al, 2020 ). The DArTseq method reduces the complexity of the genome through digestion with restriction enzymes followed by sequencing of short reads, predominantly corresponding to the active genes ( Tomkowiak et al, 2021 ). The GBS and DArTseq genotyping platforms produce high-throughput and abundant SNP markers that have been widely utilized to estimate genetic variation, discover causative allelic variations, and understand the contributing genetic architecture of complex traits with economic importance ( Baloch et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach can generate SNP markers with higher numbers covering the plants’ whole genome ( Akbari et al, 2006 ; Raman et al, 2014 ; Barilli et al, 2020 ) and is successfully used in several crops, including pea ( Aznar-Fernández et al, 2020 ). The DArTseq method reduces the complexity of the genome through digestion with restriction enzymes followed by sequencing of short reads, predominantly corresponding to the active genes ( Tomkowiak et al, 2021 ). The GBS and DArTseq genotyping platforms produce high-throughput and abundant SNP markers that have been widely utilized to estimate genetic variation, discover causative allelic variations, and understand the contributing genetic architecture of complex traits with economic importance ( Baloch et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Maize populations have been genotyped using several methods, such as Random Amplified Polymorphic DNA (RAPD) ( Carvalho et al., 2004 ), RFLP ( Garcia et al., 2004 ), and AFLP ( Schrag et al., 2006 ). The SNPs are the most widely used markers for assessing the genetic diversity and association mapping in maize ( Dos Santos et al., 2016 ; Kasoma et al., 2020 ; Tomkowiak et al., 2021 ). The SNPs can be observed through various experimental protocols.…”
Section: Genomic-assisted Techniques To Accelerate Striga ...mentioning
confidence: 99%
“…5871—SNP) linked to fusarium resistance in maize have been localized within genes [ 59 ] on chromosomes 2 and 3, respectively. In their study, Tomkowiak et al [ 60 ], using DArTseq technology and association mapping, identified six markers associated with vigor and germination in maize. The existing literature indicates that four of these genes (phosphoinositide phosphatase sac7 isoform ×1 gene, grx_c8-glutaredoxin subgroup iii gene, sucrose synthase 4 isoform ×2 gene and putative SET domain-containing protein family isoform ×1 gene) determine the level of seed germination and seed vigor in maize.…”
Section: Discussionmentioning
confidence: 99%